Flight range extension in Polistes simillimus Zikán, 1951 (Hymenoptera, Vespidae) - Prezoto,Fábio (2005)
The aim of this study was to determine the flight range extension of the social wasps, Polistes simillimus. The results of the 125 wasps-carried out tests originating from 10 colonies in post-emergency stage demonstrated that the flight range extension of P. simillimus was of approximately 150m, resulting in a collection area of about 70.650m² by colony. It suggested wasp's efficiency as a biological control agent.